Genetic Diversity and Functional Analysis of Sigma Factors in Enterobacter cloacae Complex Resourced From Various Niche. (5th February 2018) - Nazir, Farah; Ibrahim, Muhammad; Zaman, Ghunva; Hussain, Annam; Yar, Asma Muhammad; Bo, Zhu
Sigma factors are bacterial transcription factors that bind the core RNA polymerase and direct transcription initiation at a specific promoter site. These specialized sigma factors bind the promoters of genes appropriate to the environmental conditions and selectively increase the transcription of those genes. Here, we attempt to identify sigma factors in 5 genomes belonging to the Enterobacter cloacae complex (Ecc), a group of gram-negative bacteria that are important nosocomial pathogens. This process includes the identification of orthologous sequences, conserved motifs, domains, families, phylogenetic profiles, and protein-protein associations of these components. Based on the reference genome, genome-wide comparison revealed that the genomes of Enterobacter asburiae JCM6051, Enterobacter nimipressuralis CIP 104980, Enterobacter hormaechei ATCC49162, Enterobacter kobei JCM 8580, and Enterobacter ludwigii EN-119 encode 10 sigma factors that exist in the reference strain Enterobacter cloacae subsp cloacae ATCC13047. Moreover, the sequence similarity, protein domains and families of the sigma factors, protein-protein association, and phylogenetic profile indicate that the sigma factor proteins of these 5 strains may have evolutionary relatedness and functional characteristics important to their various environmental niches. Interestingly, the absence of RpoS in E kobei, which contributes to bacterial survival under environmental stress conditions, indicates that RpoS might have been independently acquired and may play different roles relating to pathogenicity, host range determination, and/or niche adaptation. Future work such as RNA sequencing will be directed towards investigating the roles that these sigma factors play in the biology of the Ecc .